2013
DOI: 10.1111/cea.12111
|View full text |Cite
|
Sign up to set email alerts
|

Dietary long chain n‐3 polyunsaturated fatty acids prevent allergic sensitization to cow's milk protein in mice

Abstract: Dietary n-3 LCPUFA largely prevented allergic sensitization in a murine model for cow's milk allergy by suppressing the humoral response, enhancing local intestinal and systemic Treg and reducing acute allergic symptoms, suggesting future applications for the primary prevention of food allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 60 publications
2
56
1
Order By: Relevance
“…Cells were permeabilized for intracellular staining by using the Foxp3 staining buffer set, according to the manufacturerÕs protocol (eBioscience). Flow cytometry was conducted by using a fluorescence-activated cell sorter (FACS Canto II; BD) and analyzed with Flowlogic Software (Inivai Technologies) (29). by a standard IL-13 flex set and Th1/Th2/Th17 kit (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were permeabilized for intracellular staining by using the Foxp3 staining buffer set, according to the manufacturerÕs protocol (eBioscience). Flow cytometry was conducted by using a fluorescence-activated cell sorter (FACS Canto II; BD) and analyzed with Flowlogic Software (Inivai Technologies) (29). by a standard IL-13 flex set and Th1/Th2/Th17 kit (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Beneficial effects of fish oil supplementation are supported by experimental studies showing reduced food allergy in mice fed a diet rich in fish oil (16). We have previously shown that a diet rich in DHA suppresses the humoral response and acute allergic symptoms to the cow milk protein whey by enhancing regulatory T cells (17,18).…”
Section: Introductionmentioning
confidence: 93%
“…As a follow-up to our previous study about the effects of a DHA-rich diet on whey allergy (17), we compared the efficacy of dietary intervention with fish oil high in EPA vs. DHA in the ability to prevent allergic symptoms in mice orally sensitized with peanut extract (PE) or whey and in mice passively immunized with PE or whey hyperimmune serum.…”
Section: Introductionmentioning
confidence: 99%
“…LCPUFA-rich fish oil is able to enhance intestinal and systemic T reg cells and reduce allergic symptoms in murine models allergic to whey or peanuts [105][106][107]. The beneficial effects of n-3 PUFAs in food allergies are probably related to the enrichment of commensal bacteria, like Lactobacillus and Bifidobacteria, and the reduction of immune cell infiltration in responsive to n-3 PUFA supplement [108].…”
Section: Diet As a Microbiome-mediated Therapeutic Toolmentioning
confidence: 99%